Building Image, Driving Performance: The Synergy of Green HRM and Employer Branding - Citta, Andi Batary; Putro, Guntur Suryo; Arfiany, Arfiany; Galib, Mukhtar (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines how Green Human Resource Management (GHRM) and Perceived Organizational Support (POS) shape employer branding and company performance in Indonesia’s digital startups. The contribution lies in extending Resource-Based View and Signaling Theory by positioning green practices and organizational support as strategic resources and credible signals that influence branding pathways rather than direct performance. A survey of 255 employees and driver-partners analyzed with PLS-SEM shows that GHRM builds employer branding but does not directly raise performance, while POS improves both branding and performance. Employer branding emerges as the key mediator that converts internal practices into external outcomes. The findings offer clear guidance for digital startup leaders: invest in green HR and supportive climates not for immediate financial gain, but for the long-term branding strength that sustains competitiveness.